Arisaema liemiana (Araceae: Arisaemateae), a new species from southern Central of Vietnam - Luu, Hong Truong; Nguyen, Quoc Dat; Nguyen, Hieu Cuong; Van, Hong Thien; Nguyen, van Du (Phytotaxa, 2020)
Arisaema liemiana is described and illustrated as a new species from Vietnam. A morphological comparison between the new and other species with yellow spathe limb in the sect. Attentuata is discussed.